Communication Variables That Influence Job Performance: A Study of Subject Matter Specialists in Indonesia - Sangun, Enisar (1999)
Job performance of staff is one of the important issues in any organisation. However, previous studies showed that job performance of Subject Matter Specialists (SMSs) at the Assessment Institute for Agricultural Technologies (AIATs) and local AIATs was very low. Poor communication has been cited as the major cause of the problem. As such this study was conducted to determine the important communication variables that influence job performance of SMSs. A sample of 123 respondents were obtained to represent 178 SMSs at AIATs/Local AIATs throughout Indonesia using stratified random sampling procedure. A structured questionnaire was used as a research instrument and the mail survey method was used to collect the relevant data. The statistical techniques used to analyse the data were descriptive statistics, t-test, one-way ANOVA, Pearson's Product Moment Correlation and multiple regression. The findings revealed that, in terms of credit points achieved, about one half of the respondents could be categorised as low performers. Credit points achieved had a significant positive relationship with four communication ability variables. Positive relationships were also found between cooperation dimension of job performance and three groups of independent communication variables, namely, communication abilities, motivational factors, and communication resources. Two variables, the ability of SMSs to establish communication network and their ability to use communication technology, were found to be good predictors of credit points. The ability of SMSs to secure feedback from clients, the adequacy of support of technical staff, and the willingness of peers to help SMSs job were significant predictors of cooperation between SMSs and information sources. To improve the SMSs' job performance, AIATs/Local AIATs should implement participatory approach on evaluating task achievement of SMSs, conduct seminars/workshops to allow SMSs to participate and improve their communication ability. Besides that, to improve cooperation between the SMSs and the sources of information, AIATs/Local AIATs should provide facilities such as transport and travel allowance for SMSs to secure accurate information from clients to improve local programmes. The support of qualified technical staff would greatly enhance the feedback process and this would in turn improve job performance of SMSs.